Quantitative research, Linguistic Discrimination and the graduation in Letters: A case study in Itaperuna (RJ), Brazil. - Caetano, Joane Marieli Pereira; Souza, Sonia Maria da Fonseca; Souza, Carlos Henrique Medeiros de; Luquetti, Eliana Crispim França; Almeida, Dr. Fabrício Moraes de; Paraguassú-Chaves, Carlos Alberto; Souza, Levi Pereira Granja de; Trindade, Carlos Alberto Dolezel; Pereira, Carlos Eugênio; Guanabara, Ricardo (International Journal for Innovation Education and Research, 2021)
This article presents the perceptions of undergraduate students about Linguistic Discrimination (LD). The main objective of this study is to analyze of quantitative research view of literary scholars confronted with situations related to the mythology of linguistic prejudice, that is, to the myths that, according to Bagno (1999), are constructors of discriminatory behaviors before certain linguistic varieties.